Academic Writing Difficulties of Master’s Students - Rey-Castillo, Marisol; Gómez-Zermeño, Marcela Georgina (Revista Electrónica Educare, 2021)
Academic literacy is the process that allows the development of necessary skills for the comprehension and production of texts in the field of higher education. This literacy is built across undergraduate studies and continues even in postgraduate education, so there will always be areas of opportunity and improvement according to academic and scientific communication needs. This work aimed to identify difficulties in the academic writing of students from two online master’s programs from a university in northeastern Mexico. Through the qualitative analysis of twelve students’ texts and interviews with five teachers, it was possible to identify aspects that can be improved, such as documentation, the articulation of one’s own voice with the sources, the citation, and some drafting elements.